Numerical Simulations of Temporary Plugging-Refracturing Processes in a Conglomerate Reservoir Under Various In-Situ Stress Difference Conditions - Chen, Jiamin; Zhang, Qiang; Zhang, Jiuchang (Frontiers in Physics, 2022)
In this study, a numerical model of the conglomerate reservoir is established using ABAQUS. Cohesive elements are embedded into the numerical model to simulate the hydraulic fracturing behaviours of the conglomerate reservoir. The cohesive elements split by the high-pressure liquid flow are identified by tracing the crack propagation. A USDFLD (user-defined field variable) subroutine is used to increase the liquid flow's dynamic viscosity in these cracked cohesive elements. Using this method, ABAQUS successfully simulates the temporary plugging-refracturing processes in the conglomerate reservoir under 4 in-situ stress states. This study found that with the increase of the horizontal in-situ stress difference, the pore pressure at the fluid injection point increased correspondingly. Under the conditions of higher horizontal in-situ stress differences, more complex branch fractures were generated in the conglomerate reservoir.